Retraction Notice: “Patellar Resurfacing of Total Knee Arthroplasty: Analytical Review”. Traumatology and Orthopedics of Russia. 2014;(3):128-141. DOI: 10.21823/2311-2905-2014-0-3-128-141 - Gennadiy M. Kavalersky; Andrey P. Sereda; Alexey V. Lychagin; Sergey M. Smetanin (Travmatologiâ i Ortopediâ Rossii, 2022)
The article Patellar resurfacing of total knee arthroplasty: Analytical review published in Traumatology and Orthopedics of Russia (2014, N 3) by G.M. Kavalersky, A.P. Sereda, A.V. Lychagin, S.M. Smetanin is a duplicate of the article Patellar resurfacing of total knee arthroplasty by A.P. Sereda, A.S. Sagradyan, A.V. Lychagin published in The Department of Traumatology and Orthopedics. 2014;(3):1828. That was the reason for retraction.